Design and Development of Robotic System for Visual Inspection of Boiler Tube Inner Surface - Jalal M.F.A.; Sahari K.S.M.; Aziz M.A.; Yunos K.; Anuar A.; Ghani M.F.A.; How D.N.T. (Elsevier B.V., 2023)
Accident prevention; Boilers; Intelligent control; Optical instruments; Robotics; Robots; Smart sensors; Tubes (components); Welding; Boiler tubes; Design and Development; In-pipe inspection robot; Inspection routines; Inspection system; Localisation Systems; Localization system; modular guide; Inspection